Clinical features, therapeutic interventions and long-term aspects of hemolytic-uremic syndrome in Norwegian children: a nationwide retrospective study from 1999–2008. Issue 1 (December 2016) - Jenssen, Gaute; Vold, Line; Hovland, Eirik; Bangstad, Hans-Jacob; Nygård, Karin; Bjerre, Anna
Abstract Background Hemolytic-uremic syndrome (HUS) is a clinical triad of microangiopathic hemolytic anemia, impaired renal function and thrombocytopenia, primarily affecting pre-school-aged children. HUS can be classified into diarrhea-associated HUS (D+ HUS), usually caused by Shiga toxin-producingEscherichia coli (STEC), and non-diarrhea-associated HUS (D− HUS), both with potentially serious acute and long-term complications. Few data exists on the clinical features and long-term outcome of HUS in Norway. The aim of this paper was to describe these aspects of HUS in children over a 10-year period. Methods We retrospectively collected data on clinical features, therapeutic interventions and long-term aspects directly from medical records of all identified HUS cases <16 years of age admitted to Norwegian pediatric departments from 1999 to 2008. Cases of D+ HUS and D− HUS are described separately, but no comparative analyses were possible due to small numbers. Descriptive statistics are presented in proportions and median values with ranges, and/or summarized in text. Results Forty seven HUS cases were identified; 38 D+ HUS and nine D− HUS. Renal complications were common; in the D+ HUS and D− HUS group, 29/38 and 5/9 developed oligoanuria, 22/38 and 3/9 needed dialysis, with hemodialysis used most often in both groups, and plasma infusion(s) were utilized in 6/38 and 4/9 patients, respectively. Of extra-renal complications, neurological complications occurred in 9/38 and 2/9, serious gastrointestinal complications in 6/38 and 1/9, respiratory complications in 10/38 and 2/9, and sepsis in 11/38 and 3/9 cases, respectively. Cardiac complications were seen in two D+ HUS cases. In patients where data on follow up ≥1 year after admittance were available, 8/21 and 4/7 had persistent proteinuria and 5/19 and 4/5 had persistent hypertension in the D+ HUS and D− HUS group, respectively. Two D+ HUS and one D− HUS patient were diagnosed with chronic kidney disease and one D+ HUS patient required a renal transplantation. Two D+ HUS patients died in the acute phase (death rate; 5 %). Conclusions The HUS cases had a high rate of complications and sequelae, including renal, CNS-related, cardiac, respiratory, serious gastrointestinal complications and sepsis, consistent with other studies. This underlines the importance of attention to extra-renal manifestations in the acute phase and in renal long-term follow-up of HUS patients.